Venetoclax Plus Gilteritinib for FLT3-Mutated Relapsed/Refractory Acute Myeloid Leukemia. Issue 35 (10th December 2022) - Daver, Naval; Perl, Alexander E.; Maly, Joseph; Levis, Mark; Ritchie, Ellen; Litzow, Mark; McCloskey, James; Smith, Catherine C.; Schiller, Gary; Bradley, Terrence; Tiu, Ramon V.; Naqvi, Kiran; et al.
Abstract : PURPOSE: The FMS-related tyrosine kinase 3 (FLT3) inhibitor gilteritinib is standard therapy for relapsed/refractory FLT3 -mutated ( FLT3 mut ) acute myeloid leukemia (AML) but seldom reduces FLT3 mut burden or induces sustained efficacy. Gilteritinib combines synergistically with the BCL-2 inhibitor venetoclax in preclinical models of FLT3 mut AML. METHODS: This phase Ib open-label, dose-escalation/dose-expansion study (ClinicalTrials.gov identifier: NCT03625505 ) enrolled patients with FLT3 wild-type and FLT3 mut (escalation) or FLT3 mut (expansion) relapsed/refractory AML. Patients received 400 mg oral venetoclax once daily and 80 mg or 120 mg oral gilteritinib once daily. The primary objectives were safety, identification of the recommended phase II dose, and the modified composite complete response (mCRc) rate (complete response [CR] + CR with incomplete blood count recovery + CR with incomplete platelet recovery + morphologic leukemia-free state) using ADMIRAL phase III–defined response criteria. RESULTS: Sixty-one patients were enrolled (n = 56 FLT3 mut ); 64% (n = 36 of 56) of FLT3 mut patients had received prior FLT3 inhibitor therapy. The recommended phase II dose was 400 mg venetoclax once daily and 120 mg gilteritinib once daily. The most common grade 3/4 adverse events were cytopenias (n = 49; 80%). Adverse events prompted venetoclax and gilteritinib dose interruptions in 51% and 48%, respectively. The mCRc rate for FLT3 mut patients was 75% (CR, 18%; CR with incomplete blood count recovery, 4%; CR with incomplete platelet recovery, 18%; and morphologic leukemia-free state, 36%) and was similar among patients with or without prior FLT3 inhibitor therapy (80% v 67%, respectively). The median follow-up was 17.5 months. The median time to response was 0.9 months, and the median remission duration was 4.9 months (95% CI, 3.4 to 6.6). FLT3 molecular response (< 10 −2 ) was achieved in 60% of evaluable mCRc patients (n = 15 of 25). The median overall survival for FLT3 mut patients was 10.0 months. CONCLUSION: The combination of venetoclax and gilteritinib was associated with high mCRc and FLT3 molecular response rates regardless of prior FLT3 inhibitor exposure. Dose interruptions were needed to mitigate myelosuppression.